Case study on Grameenphone: current scenario of post-paid package & 3G licensing of Grameenphone and their future prospects - Jebin, Laila (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.